Analisis Efisiensi Belanja Modal terhadap Pertumbuhan Ekonomi Daerah di Indonesia : Pendekatan Data Panel - Dwi Citra Haryati; Nurpiji Nurpiji; Gustina Masitoh; Wahyu Saputra; Taufik Subarkah (BADAN PENERBIT STIEPARI PRESS, 2025)
Regional economic growth is one of the main indicators for assessing the success of development, and it is significantly influenced by the effectiveness and efficiency of public budget management, particularly capital expenditure. Within the framework of fiscal decentralization, the efficiency of capital expenditure allocation by local governments becomes a crucial factor in enhancing productivity, creating economic added value, and promoting equitable distribution of public welfare. This study aims to examine the effect of capital expenditure efficiency on economic growth at the district/city level in Aceh Province using a panel data approach. The approach employed is quantitative in nature, utilizing secondary data from the Central Bureau of Statistics (BPS) over an annual time period. The analysis is conducted using a panel data regression model, and based on the Chow and Hausman tests, the Random Effect Model (REM) is selected as the most appropriate model. The estimation results indicate that capital expenditure has a positive and significant effect on regional economic growth, suggesting that government investment through capital spending can stimulate economic activity and enhance the region’s production capacity. These findings are in line with endogenous growth theory, which emphasizes the importance of government spending as a key driver of long-term economic development. This study provides an important contribution to the literature on regional economics and offers fiscal policy implications, particularly in improving the effectiveness and efficiency of development spending. For future research, it is recommended to expand the study to a broader regional scope and consider additional control variables such as institutional quality, infrastructure conditions, and other socio-economic indicators to obtain a more comprehensive understanding of public expenditure effectiveness.